High Quality Paper award IEEE PES 2013 PowerTech - Aristidou, Petros (My University, 2026)
High Quality Paper award for paper ’Dynamic Simulations of Combined Transmission and Distribution Systems using Decomposition and Localization’, IEEE PES 2013 PowerTech, Grenoble (honorary diploma). Role: main author
Keywords: Sciences